PENGARUH ABILITY, MOTIVASI DAN PENGEMBANGAN KARIR TERHADAP KINERJA KARYAWAN REDAKSI PT RIAU POS INTERMEDIA PEKANBARU - Abdul Kadir '; Marnis ' '; Machasin ' ' (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2014)
This reasearch aims to reveal the influence of ability, motivation and career development factor on the performance of editorial employees at PT. Riau Pos Intermedia Pekanbaru. The research was conducted at PT. Riau Pos Intermedia Pekanbaru. Targeted population wereeditorial employees of PT. Riau Pos Intermedia Pekanbaru totaling 116 people, sampling was conducted with cluster purposive sampling technique. The entire samples in the research were as many as 90 employees. The objects of the research as independent variables were ability, motivation, and career development factor, while the dependent variable applied was employee performance. Hypothesis testing was performed by applying multiple regression analysis model. The research’s result showed that the variableof ability, motivation and career development simultaneously had significant performance in which the calculated F was greater than F table. While two variables which had partial significant influence were the ability variable where t was greater than t table; 8,210 > t - table 1.98 and motivation variable; 3.023 > 1.98. While career development variable did not affect the performance of which was -1.544 t < t - table 1.98 and with significance 0.126 >α 5 % . It can be concluded that ability, motivation and career development simultaneously had significant effect on the performance variable. While partial ability and motivation variable significantly influenced employee performance. From the result,it is suggested that the company management increase employee capability and motivate the employees to improve their performance. Kata Kunci : Ability, motivation, career, performance and editor.